Integrasi Islam, Sains, dan Budaya Nusantara di Perguruan Tinggi Islam Swasta dan Relevansi di UII Yogyakarta - Ulfiyani Mungasiroh; Moh Roqib (Journal on Education, 2024)
Private Islamic universities increasingly emphasize the importance of integrating Islam, science and culture in their curriculum and campus life. This model aims to create a balanced learning environment, combining Islamic values with science and local culture. The structured curriculum offers a holistic approach, strengthening Islamic identity in forming students' character. Through religious, scientific and cultural activities, students are actively involved in character formation and developing practical skills. Continuous evaluation and monitoring are key in ensuring the effectiveness of this integration, while active engagement with the community strengthens the contribution of universities to community development. Thus, the integration of Islam, science and culture in private Islamic universities provides a strong foundation for the formation of holistic and globally competitive individuals with a strong identity.